Educational materials analyse used as a tool for environmental eduaction for students of public schools in Rio de Janeiro - Teixeira, Robson da Silva; Souza, Rodrigo Otavio Lopes de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
This study aims to identify and analyze the printed educational materials on environmental education available for professionals in education in the municipality of Rio de Janeiro, with the research environment, the collection belonging to the CIEP Teacher Caesar Pernetta library and legal issues involved in process of inclusion of educational materials in the classroom of public schools in the city plan of Rio de Janeiro (RJ). It was noticed, the precariousness of these on the content and the language used in relation to environmental education. This analysis, however, does not intend to discourage the use of auxiliary materials, another yes, reassess the way they are designed and made available on the public network of Rio de Janeiro.